The impact of citizen journalism towards society / Nur Maisarah Mohd Yunos ... [et al.]. - Mohd Yunos, Nur Maisarah; Mohd Fadzly, Nurqistina; Aminuddin, Muhammad Haikal; Nasaruddin, Nurul Syafiqah; Zulkefle, Muhammad Najmi (2019)
Journalism refer to an activity or product that engaged in the preparation 111 written, visual or audio material which will be spread through public media with reference to factual, ongoing event to the public concern. It also known as the activity of gathering or presenting of the news and information. In Malaysia, journalist will have the advantage of which they are the first person to receive information from their trusted sources. This trend of journalist leads the society to become a journalist or also known as the citizen journalism which mean that the job conducted by people who are not professional journalists but who disseminate information using social media or internet such as blog and website. Citizen journalism has expanded its worldwide influence despite continuing concerns over whether citizen journalists are as reliable as trained professionals. According to Courtney C. Rad sch, which defines citizen journal ism "as an alternative and activist form of newsgathering and reporting that functions outside mainstream media institutions, often as a repose to shortcoming in the professional journalistic field. That uses similar journalistic practices but is driven by different objectives and ideals and relies on alternative sources of legitimacy than traditional or mainstream journalism."